Voltammetric behavior of triazole fungicides on boron doped diamond electrode - Šelešovská, Renáta; Krejčová, Kateřina; Schwarzová, Karolína; Janíková, Lenka; Chýlková, Jaromíra (BEST Servis, 2019)
Voltammetric behavior of azole fungicides difenoconazole, tebuconazole, and triticonazole was investigated for the first time using boron doped diamond electrode. Oxidation mechanism was also solved. The obtained oxidation signals of particular compounds were utilized for the development of voltammetric methods for their determination. Proposed methods were applied for analysis of real samples, e.g., spiked drinking and natural water, pesticide preparations.
Voltametrické chování triazolových fungicidů na elektrodě z borem dopovaného diamantu
Keywords: Azole fungicides; Difenoconazole; Tebuconazole; Triticonazole; Oxidation; Boron doped diamond electrode; Azolové fungicidy; Difenoconazol; Tebuconazol; Triticonazol; Oxidace; Elektroda z borem dopovaného diamantu